Imam et Mahdi : Ibn Abî Mahallî - Mercedes García-Arenal (Revue des Mondes Musulmans et de la Méditerranée)
Ibn Abî Mahallî (d. 1643) was the last mahdi to have taken political power in Morocco. This article makes use of three types of sources :the works of Ibn Abî Mahallî himself, contemporary and later Arabic sources - which invariably support the ruling dynasty - and finally, documents from European archives written by contemporary merchants or agents. This variety of sources permits one to study the range of ideas concerning Ibn Abî Mahallî from the expectations and beliefs of the followers to the doctrinal construction developed by Ibn Abî Mahalli himself. They allow one to perceive which elements and which aspects of an individual's thought came to acquire public legitimacy and the manner in which this happened.